Effects of the flow diversion technique on nucleotide levels in intra-cranial aneurysms: A feasibility study providing new research perspectives - Eker, Omer F.; Lubicz, Boris; Cortese, Melissa; Delporte, Cedric; Berhouma, Moncef; Chopard, Bastien; Costalat, Vincent; Bonafé, Alain; Alix-Panabières, Catherine; Van Anwterpen, Pierre; Zouaoui Boudjeltia, Karim (Frontiers in Cardiovascular Medicine, 2022)
Introduction The flow diverter stent (FDS) has become a first-line treatment for numerous intra-cranial aneurysms (IAs) by promoting aneurysm thrombosis. However, the biological phenomena underlying its efficacy remain unknown. We proposed a method to collect in situ blood samples to explore the flow diversion effect within the aneurysm sac. In this feasibility study, we assessed the plasma levels of nucleotides within the aneurysm sac before and after flow diversion treatment. Materials and methods In total, 14 patients with unruptured IAs who were selected for FDS implantation were prospectively recruited from February 2015 to November 2015. Two catheters dedicated to (1) FDS deployment and (2) the aneurysm sac were used to collect blood samples within the parent artery (P1) and the aneurysm sac before (P2) and after (P3) flow diversion treatment. The plasma levels of adenosine monophosphate (AMP), adenosine diphosphate (ADP), and adenosine triphosphate (ATP) at each collection point were quantified with liquid chromatography and tandem mass spectrometry. Results The aneurysms were extradural in nine (64.3%) patients and intra-dural in five (35.7%) patients. They presented an average diameter of 15.5 ± 7.1 mm, height of 15.8 ± 4.6 mm, and volume of 2,549 ± 2,794 ml. In all patients (100%), 16 FDS implantations and 42 in situ blood collections were performed successfully without any complications associated with the procedure. The ATP, ADP, and AMP concentrations within the aneurysm sac were decreased after flow diversion (p = 0.005, p = 0.03, and p = 0.12, respectively). Only the ATP levels within the aneurysm sac after flow diversion were significantly correlated with aneurysm volume (adjusted R2 = 0.43; p = 0.01). Conclusion In situ blood collection within unruptured IAs during a flow diversion procedure is feasible and safe. Our results suggest that the flow diversion technique is associated with changes in the nucleotide plasma levels within the aneurysm sac.